Studi Analisis Dampak Akulturasi Budaya Terhadap Sikap Ukhuwwah Islamiyyah Mahasiswa dalam Dimensi Globalisasi - Mohammad Rindu Fajar Islamy; Muhamad Parhan; Jenuri Jenuri; Dina Mayadiana Suwarma (Transformatif, 2021)
The flow of globalization has had a huge impact on cultural and cultural changes that have developed in modern society. Indonesia is a country that has diversity and differences in ethnicity, customs, culture, and culture so this can certainly be a multidimensional conflict that is not managed properly. One of the solutions offered by the religion of Islam in minimizing this potential is to improve the attitudes and behavior of the ukhuwwah Islamiyyah among Muslims. This research study aims to examine and examine the impact of cultural acculturation on the attitude of ukhuwwah Islamiyyah among university students. The research method used a quantitative approach by applying an analytic descriptive study. Using a random sampling technique, participants took from 43 student respondents from the Faculty of Education. The value measurement technique uses a Likert scale. The variable components of ukhuwwah Islamiyyah are divided into four, namely mutual help, tolerance, friendship, and obligations to fellow Muslims. The results showed that globally the attitude of ukhuwwah Islamiyyah had a good predicate. Students with a cultural background of Bugis get a score of 75%, then Javanese culture is 72.89%, Malay 77.50%, Minang 78%, Sundanese 74.70%, and a combination of Javanese and Sundanese culture is 77.50%. This assessment illustrates that culture has a strategic role in shaping the attitude of ukhuwwah Islamiyyah for university students in the world of modernity.